PHONETIC AND PHONOLOGICAL ASPECTS OF SPEECH REDUCTION IN ENGLISH. (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Speech reduction is a central phenomenon in conversational English, involving changes to the phonetic and phonological features of words. These changes often make speech faster, more efficient, but less distinct, leading to challenges for non-native listeners, language learners, and automatic speech recognition systems. This article explores the phonetic and phonological aspects of speech reduction, the factors influencing its occurrence, and its implications for linguistic theory, language acquisition, and computational linguistics.